Pengaruh Variasi Latihan Berpasangan Terhadap Keterampilan Sepak Sila dalam Permainan Sepak Takraw Pada Siswa Putra Peserta Ekstrakulikuler Sepak Takraw Di Smp Negeri 1 Conggeang Tahun Pelajaran 2023/2024 - Supriadi, Firyal Khairunisa; Hermawan, Dadang Budi; Soleh, Mirwan Aji (JPSA - Jurnal PJOK Sebelas April, 2025)
Sepak sila itself is the most important technique in the game of sepak takraw. Sepak sila also has a variety of functions that are used to feed or pass the ball to friends, receive the opponent's ball, return the ball from the opponent, and also save the opponent's attack. Therefore, a player is required to have good sila soccer skills in order to be able to play sepak takraw well too. The problem encountered by students at SMP Negeri 1 Conggeang in the implementation of extracurricular activities is that there are still many students who have limitations and do not have good abilities in performing the sepak sila technique, this is because students are only told to do the movements directly without being given examples and also variation methods, sometimes students also directly game or play. The limitations that exist can cause a lack of sila soccer skills in students. The objectives of this study were a. to determine the effect of variations in paired training on sila soccer skills in extracurricular participants at SMP Negeri 1 Conggeng and b. to determine how much influence the variation of paired training has on sila soccer skills in extracurricular participants at SMP Negeri 1 Conggeang. This research method uses an experiment with a pretest-post test design. The population of this study was 15 male students participating in sepak takraw extracurricular at SMP Negeri 1 Conggeang with a sample of 15 students. The instrument used is a test The instrument used is the sila soccer test. The data analysis technique used uses the liliefors test and the t test. Based on the calculations obtained data that there is an increase between the initial test and the final test after being given the treatment of paired variation training on sila soccer skills in sepak takraw game amounting to Thitung = 9.732>Ttabel = 2.1448. This means that there is an effect of variations in paired training on sila soccer skills in sepak takraw games.